Distribution of demersal fish assemblages along the west coast of St Lucia: Implications for planning no‐take marine reserves. Issue 6 (10th February 2021) - Mitchell, Peter J.; Bolam, Stefan G.; Close, Hayden L.; Garcia, Clement; Monk, Jacquomo; Alliji, Khatija
Abstract: Evidence‐based decisions relating to effective marine protected areas as a means of conserving biodiversity require a detailed understanding of the species present. The Caribbean island nation of St Lucia is expanding its current marine protected area network by designating additional no‐take marine reserves on the west coast. However, information on the distribution of fish species is currently limited. This study used baited remote underwater stereo‐video to address this shortcoming by investigating the effects of depth and seabed habitat structure on demersal fish assemblages and comparing these assemblages between regions currently afforded different protection measures. From the 87 stations visited a total of 5, 921 fish were observed comprising 120 fish taxa across 22 families. Species richness and total abundance were higher within the highly managed region, which included no‐take reserves. Redundancy analysis explained 17% of the total variance in fish distribution, driven predominantly by the seabed habitats. The redundancy analysis identified four main groups of demersal fishes each associated with specific seabed habitats. The current no‐take marine reserves protected two of these groups (i.e. fishes associated with the 'soft corals, hard corals or gorgonians' and 'seagrass' groups). Importantly, habitats dominated by sponges, bacterial mats, algal turfs or macroalgae, which also supported unique fish assemblages, are not currently afforded protection via the marine reserve network (based on the five reserves studied). These results imply that incorporation of the full breadth of benthic habitat types present would improve the efficacy of the marine reserve network by ensuring all fish assemblages are protected.